Role of Vitamin E and Vitamin A in Oral Mucositis Induced by Cancer Chemo/Radiotherapy- A Meta-analysis - Chaitanya, Nallan Csk (Journal of clinical and diagnostic research, 2017)
Oral mucositis is known to hamper the quality of life in patients treated for oral cancer. Many pharmacological agents have been tried and tested in its management, especially vitamin supplements including A, E and their combinations. A Meta-analysis was carried out to evaluate the efficacy of vitamins individually used for prevention or treatment of oral mucositis separately for chemotherapy, concurrent chemo radiotherapy, radiotherapy and Haematopoietic Stem Cell Transplantation (HSCT) individuals. The literature study was done using PUBMED, MEDLINE, EBSCO, GOOGLE SCHOLAR and COCHRANE data bases with keywords vitamin A, vitamin E, vitamin B, vitamin C, Oral mucositis, Chemotherapy, Radiotherapy, Concurrent chemo radiotherapy and Haematopoietic stem cell transplantation individually, from the year 1980 to 2016. Only randomized controlled trials were included. The data was extracted, tabulated and was subjected to statistical analysis with CI of 95%. Among 201 subjects the analysis clearly demonstrated a male predominance to females in studies where male to female ratio was given. Out of 8 studies, 2 were studies in children and remaining 6 studies concentrated on adult population. WHO and NCI-CTC criteria were followed except for one study which used customised assessment. A meta-analysis was performed regarding usage of topical medication of Vitamin E group in all three cancer treatment modalities, which showed significant reduction in oral mucositis (p < 0.001). There was reduced oral mucositis in a small group of patients with Vitamin A when compared to controls. No information on the agent used for chemotherapy, the dose of radiotherapy and the type of tumours in 4 studies. Topical Vitamin E had performed better on oral mucositis than Vitamin E systemic administration. Though the efficacy of topical treatment with Vitamin A showed reduction in oral mucositis, it was evaluated in a very small sample which cannot be attributed to a larger sitting.